Electromagnetism calculation of single‐sided linear induction motor with transverse asymmetry using finite‐element method. Issue 1 (1st January 2016) - Lv, Gang; Liu, Zhiming; Sun, Shouguang
Abstract : Electromagnetic variations of the single‐sided linear induction motor (SLIM) are calculated by three‐dimensional (3D) finite‐element method (FEM) when the primary is displaced sideways from a symmetrical position. For geometrical and electrical asymmetry, a full 3D model, which considering the longitudinal and transverse end effects, overhangs of the primary windings and secondary, as well as lateral displacement, is developed. Apart from the thrust and vertical force, lateral force is produced when the transverse asymmetry occurred. Hence, the calculation equation of thrust, vertical and lateral forces in each element of the 3D FEM model and boundary conditions are presented. Air‐gap flux densities along the longitudinal and transverse directions with different lateral displacements are obtained, as well as the distortion coefficients of the air‐gap flux density is proposed. Corresponding induced currents in the secondary are predicted. Finally, the variations of the thrust, vertical and lateral forces are experimentally validated by measurements on reciprocal power‐fed test rig. It shows that the flux in between overhangs of the primary winding and secondary has great effect on the lateral force, the thrust and vertical force decrease with the increase of the lateral displacement.